Comparative study of onion (Allium cepa L.) seed quality in relation to storage containers and duration - Hossain, M S; Sarkar, M J; Al Islam, M Z; Jannat, S A; Begum, M N S; Mahmud, A (Bangladesh Journal of Nuclear Agriculture, 2025)
Onion (Allium cepa L.) is an essential bulbous vegetable and condiment crop known for having some of the shortest-lived seeds among common vegetable crops. These seeds quickly lose their viability after harvest unless special storage precautions are taken. An experiment was conducted to determine the effects of storage containers and durations on the quality of onion seeds at the Seed Technology Laboratory, Gazipur Agricultural University (GAU), Gazipur, Bangladesh from April to June 2024. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications, where two storage containers (plastic jar and cloth bag) and four storage periods (15, 30, 45, and 60 days) were used as treatments to assess the seed quality status of onions. The onion seeds stored in a plastic jar exhibited better germination capacity, as indicated by a high germination index, higher root and shoot lengths of the seedlings, seedling dry weight per plant, and a high vigor index. On the contrary, higher thousand seed weight, moisture content, and electrical conductivity were recorded in the cloth bag seed, indicating lower seed quality during the testing period. The moisture content, thousand seed weight, and electrical conductivity increased with the longer duration of storage. In addition, germination index, seedling root length, seedling shoot length, seedling dry weight per plant, and vigor index decreased with the increase in storage duration. The results suggested that the plastic jar maintained a better quality of onion seeds over the storage periods compared to the cloth bag. Bangladesh J. Nuclear Agric., 39(1): 115-128, 2025